2017
DOI: 10.1111/jace.14817
|View full text |Cite
|
Sign up to set email alerts
|

The influence of composition and temperature on hydrated phase assemblages in magnesium oxychloride cements

Abstract: Due to their nonhydraulic nature, magnesium oxychloride cements (MOCs) are susceptible to degradation following contact with water. Improving the water resistance of these materials requires better understanding of hydrated phase relations and the sensitivity of hydrated phases to water. Toward this end, a series of targeted experiments and complementary thermodynamic calculations were carried out to assess hydrated phase assemblages in the system MgO-MgCl 2 -H 2 O across a range of compositions. Focus is plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…It should be noted that for all the MOC specimens, the mineralogical phases consist of major Phase 5, minor Mg(OH) 2 and unreacted MgO and MgCO 3 . This is in agreement with the previous studies [2,4,6]. As the Phase 5 is the most favourable crystalline phase [2,6], the molar ratio of MgO/MgCl 2 is desired to be higher than 5 and the molar ratio of H 2 O/MgCl 2 is in the range of 6-15.…”
Section: Crystalline Compositionsupporting
confidence: 91%
See 1 more Smart Citation
“…It should be noted that for all the MOC specimens, the mineralogical phases consist of major Phase 5, minor Mg(OH) 2 and unreacted MgO and MgCO 3 . This is in agreement with the previous studies [2,4,6]. As the Phase 5 is the most favourable crystalline phase [2,6], the molar ratio of MgO/MgCl 2 is desired to be higher than 5 and the molar ratio of H 2 O/MgCl 2 is in the range of 6-15.…”
Section: Crystalline Compositionsupporting
confidence: 91%
“…Magnesium oxychloride cement (MOC) has attracted extensive attention, as it is generally associated with ambient temperature curing and excellent materials properties such as fast setting, high mechanical strength, good resistance to abrasion and fire [1][2][3][4][5]. The behavior of MOC is mainly regulated by the composition and microstructure of the hydration products, produced through neutralization-hydrolysis-crystallization process in the ternary system of MgO-MgCl 2 -H 2 O [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…It has early been concluded that the aqueous reactions between MgO and MgCl 2 in the system MgO‐MgCl 2 ‐H 2 O can yield Mg 3 (OH) 5 Cl·4H 2 O (5‐phase), Mg 2 (OH) 3 Cl·4H 2 O (3‐phase), Mg(OH) 2 , the gel and mixtures thereof, which are highly dependent on the precursor molar ratios, temperature, and MgO reactivity (ie, the reaction rate of MgO in MgCl 2 solution) 17‐23 . Besides, the equilibrium phases in the system also involve unreacted MgO and residual chlorides.…”
Section: Introductionmentioning
confidence: 99%
“…For structural applications, MOC has the stoichiometric formula Mg 3 (OH) 5 Cl·4H 2 O and it is commonly referred to as 5‐phase MOC . MOC has an alternative stoichiometric formula (Mg 2 (OH) 3 Cl·4H 2 O, 3‐phase MOC) that is thermodynamically more stable at low water content curing conditions, but 5‐phase is usually the preferred phase for construction applications.…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium oxychloride is known to slowly degrade in water and recrystallize into magnesium hydroxide or other magnesium species, which can be accelerated with increased temperature. This results in issues regarding the retention of structural properties of MOC composites when exposed to weathering conditions, such as rain and high humidity.…”
Section: Introductionmentioning
confidence: 99%